Case Report: A rare case of male breast synovial sarcoma - Yue, Wang; Hua, Ding; Yumei, Fu; Mengyi, Liu; Jian, Zhang; Dajiang, Song; Shu, Liu; Ke, Luo (Frontiers in Oncology, 2025)
Synovial sarcoma (SS) is a rare and aggressive malignancy that primarily affects young people and usually occurs in the extremities. Breast involvement is uncommon, and males with breast SS are even rarer. We present a rare case of a 17-year-old boy with a progressively growing mass found in his right breast, which was confirmed as SS through pathological diagnosis following surgery.